(untitled) (Research, Society and Development, 2018)
This text addresses the theme collaboration scheme in education. Its purpose is to express how the meaning and nature of the collaboration regime in the field of contemporary education has been constructed. For its systematization, it is anchored methodologically in literature review and analysis of norms and documents produced in distinct management spaces: in the Legislative Branch (Federal Constitution of 1988, National Education and Guidelines Directive 1996, National Education Plan (2014-2024) and Draft Laws), in the Executive (Ministry of Education) and in spaces designated for the democratic management of education (National Council of Education and National Conferences of Education). As results, it works with the hypothesis that it is a thesis of a good part of the public schoolers, universal, free, secular, emancipatory and of socially referenced quality in the working class that is in the system of collaboration that national education takes its meaning systemic. However, he concludes that it is not possible to conceal the emergence of the contradiction reinforced by the state model after the reform in the 1990s, and anchored in the capitalist mode of production.